Mapping Research Trends on Body Mapping as a Counseling Technique for Emotional Expression: A Bibliometric Analysis - Melinda Melinda; Vira Afriyati; Anni Suprapti (Universitas PGRI SUMATERA BARAT, 2026)
Adolescents’ emotional problems have become an important issue in Guidance and Counseling services, requiring counseling techniques that can help individuals express emotions adaptively. This study aims to map the development of Body Mapping research as a counseling technique for self-emotional expression through a Scopus-based bibliometric approach during the 2018–2025 period. Data retrieval using a Boolean search string resulted in 529 documents, which were then screened based on inclusion and exclusion criteria, resulting in 136 relevant articles. The analysis was conducted using VOSviewer and OpenRefine through publication trend analysis, keyword co-occurrence, cluster analysis, co-authorship, country distribution, subject area, and overlay visualization. The findings indicate that publications on Body Mapping have increased in recent years. Research themes are dominated by psychology, mental health, emotion, body experience, and arts-based intervention. Cluster analysis shows the relationship between psychological aspects, health, and arts-based approaches in Body Mapping studies. In addition, research has developed more widely in the contexts of psychology and health than in Guidance and Counseling. These findings indicate that Body Mapping has the potential to be developed as a nonverbal counseling technique to support emotional exploration and self-reflection in individual and group counseling services.